2016
DOI: 10.1158/1078-0432.ccr-15-2903
|View full text |Cite
|
Sign up to set email alerts
|

Transposon Mutagenesis Reveals Fludarabine Resistance Mechanisms in Chronic Lymphocytic Leukemia

Abstract: To our knowledge, this is the first forward genetic screen for chemotherapy resistance in CLL. The screen pinpointed novel genes and pathways involved in fludarabine resistance along with previously known resistance mechanisms. Transposon screens can therefore aid interpretation of cancer genome sequencing data in the identification of genes modifying sensitivity to chemotherapy. Clin Cancer Res; 22(24); 6217-27. ©2016 AACR.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…The literature suggests that patients with MAPK-ERK mutations represent a biologically distinct subgroup, where MAPK-ERK mutations are frequently mutually exclusive, are enriched for trisomy 12, unmutated IGHV genes and other adverse biological markers (e.g. CD38, ZAP-70, CD49d), and are linked to inferior time to first treatment in retrospective cohorts [41,[43][44][45]. We now show the MAPK-ERK genes, BRAF, KRAS and NRAS (collectively representing 12.2% of patients) are also independently associated with short OS in a cohort of patients requiring treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests that patients with MAPK-ERK mutations represent a biologically distinct subgroup, where MAPK-ERK mutations are frequently mutually exclusive, are enriched for trisomy 12, unmutated IGHV genes and other adverse biological markers (e.g. CD38, ZAP-70, CD49d), and are linked to inferior time to first treatment in retrospective cohorts [41,[43][44][45]. We now show the MAPK-ERK genes, BRAF, KRAS and NRAS (collectively representing 12.2% of patients) are also independently associated with short OS in a cohort of patients requiring treatment.…”
Section: Discussionmentioning
confidence: 99%
“…DDR1 gene is highly expressed in various cancer types, such as in chronic lymphocytic leukaemia (Barisione et al, 2017). In addition, BMP2K gene has been recently shown to be implicated in chronic lymphocytic leukemia (CLL) (Pandzic et al, 2016), while CHST11 has long been known to be deregulated in CLL (Schmidt et al, 2004). TNFSF11 encodes RANKL which is part of a prominent cancer signalling pathway (Renema et al, 2016) and TNFSF11 has been reported to be the most overexpressed gene in a sample of n = 129 acute lymphoblastic leukemia (ALL) patients (Heltemes-Harris et al, 2011).…”
Section: Attention Analysismentioning
confidence: 99%
“…In several studies, this method also has been used to characterize resistance mechanisms in vitro (17)(18)(19) and in mice…”
mentioning
confidence: 99%